2014
DOI: 10.1186/1756-0500-7-243
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies on the effect of (Lambda-Cyhalothrin) insecticide on lungs and the ameliorating effect of plant extracts (Ginseng (Panax Ginseng) and garlic (Allium sativum L.) on asthma development in albino rats

Abstract: BackgroundLambda-cyhalothrin (LTC) is a synthetic pyrethroid insecticide for agricultural and public health applications. This study was to determine the pathological alterations of LTC in lungs, which has not previously been studied, and the ameliorating effects of plant extracts (ginseng and garlic) on the development of asthma in albino rats.MethodsFour groups (gps) of albino rats, (n = 20, average body weight = 200 gm with an age of 4 months), were formed. Gp 1 was kept as control. Gp 2 was injected intrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…It has been reported that garlic extract protected lung and bronchial smooth muscle cell lines via increasing intracellular GSH content [14]. Our previous animal study found that dietary intake of SEC or SMC displayed anti-oxidative and anti-inflammatory protection against ethanol-induced liver injury in mice [15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that garlic extract protected lung and bronchial smooth muscle cell lines via increasing intracellular GSH content [14]. Our previous animal study found that dietary intake of SEC or SMC displayed anti-oxidative and anti-inflammatory protection against ethanol-induced liver injury in mice [15].…”
Section: Introductionmentioning
confidence: 99%
“…P. ginseng is one of most commonly used medicinal herbs to complement the treatment of asthma, allergies, and immunologic conditions [11] . Several researchers have reported that P. ginseng ameliorates asthma in animal models [12,13] , but to date, the effects of processing on its medicinal effects have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are naturally synthesized in many Allium plants including garlic and onion (Jones and others ). It has been reported that garlic extract protected lung and bronchial smooth muscle cell lines via increasing intracellular glutathione (GSH) level (Jeong and others ; Mohi El‐Din and others ). However, it remains unknown that which components in that garlic extract was responsible for these observed beneficial activities.…”
Section: Introductionmentioning
confidence: 99%